Bile reflux gastritis and Barrett's oesophagus: further evidence of a role for duodenogastro-oesophageal reflux?. Issue 3 (1st September 2001) - Dixon, M F; Neville, P M; Mapstone, N P; Moayyedi, P; Axon, A T R
Abstract : BACKGROUND: There is increasing evidence that reflux of bile plays a part in the pathogenesis of Barrett's oesophagus. Bile injury to the gastric mucosa results in a "chemical" gastritis in which oedema and intestinal metaplasia are prominent. AIM: To determine if patients with Barrett's oesophagus have more bile related changes in antral mucosa than patients with uncomplicated gastro-oesophageal reflux disease (GORD) or non-ulcer dyspepsia (NUD). PATIENTS AND METHODS: Patients were identified by a retrospective search of pathology records and those with a clinically confirmed diagnosis of either Barrett's oesophagus or reflux oesophagitis who had oesophageal and gastric biopsies taken at the same endoscopy and had no evidence of Helicobacter pylori infection entered the study. Control biopsies were taken from H pylori negative NUD patients. Antral biopsies were examined "blind" to clinical group and graded for a series of histological features from which the "reflux gastritis score" (RGS) and "bile reflux index" (BRI) could be calculated. The reproducibility of these histological scores was tested by a second pathologist. RESULTS: There were 100 patients with Barrett's, 61 with GORD, and 50 with NUD. The RGSs did not differ between groups. BRI values in the Barrett's group were significantly higher than those in GORD subjects (p=0.014) which in turn were higher than those in NUD patients (p=0.037). Similarly, the frequency of high BRI values (>14) was significantly greater in the Barrett's group (29/100; 29%) than in the GORD (9/61; 14.8%) or NUD (4/50; 8%) group. However, agreement on BRI values was "poor", indicating limited applicability of this approach. CONCLUSION: Patients with Barrett's oesophagus have more evidence of bile related gastritis than subjects with uncomplicated GORD or NUD. The presence of bile in the refluxate could be a factor in both the development of "specialised" intestinal metaplasia and malignancy in the oesophagus.